Apocryphal and esoteric sources in the development of Christianity and Judaism the Eastern Mediterranean, the Near East, and beyond - Dorfmann-Lazarev, Igor 1968- (Leiden Boston Brill, 2021)
Apocryphal traditions, often shared by Jews and Christians, have played a significant role in the history of both religions. The 26 essays in this volume examine regional and linguistic developments in Ethiopia, Egypt, Syria, Armenia, the Balkans, and Italy. Dissenting groups, such as the Samaritans, followers of John the Baptist, and mediæval dualists are also discussed. Furthermore, the book looks at interactions of Judaism and Christianity with the religions of Iran. Seldom verified or authorized, and frequently rejected by Churches, apocryphal texts had their own process of development, undergoing significant transformations. The book shows how apocryphal accounts could become a medium of literary and artistic elaboration and mythological creativity. Local adaptations of Biblical stories indicate that copyists, authors and artists conceived of themselves as living not in a post-Biblical era, but in direct continuity with Biblical personages
Includes bibliographical references and index
Keywords: Biblical Interpretation; Konferenzschrift -- 2018 -- Bad Homburg